2019
DOI: 10.1039/c9gc00811j
|View full text |Cite
|
Sign up to set email alerts
|

TixCe1−xO2 nanocomposites: a monolithic catalyst for the direct conversion of carbon dioxide and methanol to dimethyl carbonate

Abstract: Dimethyl carbonate (DMC) is widely employed as a versatile reagent and solvent for green organic synthesis and fuel additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 40 publications
2
72
2
Order By: Relevance
“…Next, Shi et al. controlled and precisely deposited the CuO nanoclusters onto the TiO 2 {101} of the TiO 2 ‐spindle, supported by TEM and photoluminescence and Raman spectroscopy [62] . CH 3 OH‐TPD showed that methanol can be chemisorbed on the CuO/TiO 2 catalyst, meaning that the CuO/TiO 2 should be a good candidate for the methanol oxidations.…”
Section: Methyl Formate (Mf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Next, Shi et al. controlled and precisely deposited the CuO nanoclusters onto the TiO 2 {101} of the TiO 2 ‐spindle, supported by TEM and photoluminescence and Raman spectroscopy [62] . CH 3 OH‐TPD showed that methanol can be chemisorbed on the CuO/TiO 2 catalyst, meaning that the CuO/TiO 2 should be a good candidate for the methanol oxidations.…”
Section: Methyl Formate (Mf)mentioning
confidence: 99%
“…An over 97 % conversion and 83 % selectivity were achieved over the CuO/TiO 2 ‐P under mild conditions (365 nm irradiation). Interestingly, the catalytic activity has a strong relationship with surface oxygen vacancy (O V ) species during the CuO/TiO 2 ‐P catalyzed reactions, [62,63] Figure 6, indicating that the CuO nanoclusters can optimally tune excitons recombination through O V generation to promote the methanol conversions. Further, in‐situ attenuated total reflection infrared spectroscopic analysis reveals, for the first time, that the methanol oxidation most likely occurs via the pathway from the adsorbed methoxy (CH 3 O*) to adsorbed formaldehyde (CHO*) species, Figure 7.…”
Section: Methyl Formate (Mf)mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Recently, development of effective catalysts to produce DMC through oxidative carbonylation of methanol, which is thermodynamically favorable has received greater attention. [6][7][8][9][10][11][12][13][14][15][16][17][18] Being, chloride-free, CuY zeolite has shown greate potential to obtain high activity and excellent selectivity for oxidative carbonylation reaction. [16][17][18][19][20][21][22][23] Generally, Cu exchanged zeolite Y, CuY was prepared by ion-exchange of NaY zeolite with the ammonia solution of copper nitrate, followed by calcination at high temperatures in an inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…There is a popular belief that the greater the proportion of Ce 3+ , the higher the degree of unsaturated of ceria, which may be beneficial to catalyst performance. Doping metal ions into ceria could create more oxygen vacancies 21,22 . Li et al studied the role of oxygen vacancy in DMC formation by doping Zr into CeO 2, 22 and they found that CO 2 could be adsorbed and activated on the oxygen vacancy sites.…”
Section: Introductionmentioning
confidence: 99%